DYSLEXIA AND DYSGRAPHIA IN THE READING AND WRITING OF ENGLISH WORDS BY UPPER-PRIMARY PUPILS FROM SELECT SCHOOLS IN SABATIA SUB-COUNTY IN KENYA (The University of Nairobi Journal of Language and Linguistics, 2023)
This study sought to investigate whether there was correlation between reading impairment (dyslexia) and writing impairment (dysgraphia), and whether function words would pose a greater challenge than content words in both reading and writing in the English of a group of twentyfive upper-primary pupils (of the Sabatia Sub-county of Vihiga County, Kenya) who experienced serious reading and writing difficulties. Itfound that there was a high positive correlation between the subjects’ reading and writing (r = 0.79 at p
Keywords: Dyslexia